2023
DOI: 10.1038/s41531-023-00444-w
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic physiological α-synuclein S129 phosphorylation is driven by neuronal activity

Abstract: In Parkinson’s disease and other synucleinopathies, the elevation of α-synuclein phosphorylated at Serine129 (pS129) is a widely cited marker of pathology. However, the physiological role for pS129 has remained undefined. Here we use multiple approaches to show for the first time that pS129 functions as a physiological regulator of neuronal activity. Neuronal activity triggers a sustained increase of pS129 in cultured neurons (200% within 4 h). In accord, brain pS129 is elevated in environmentally enriched mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 77 publications
10
37
0
Order By: Relevance
“…In the current study, Ramalingam et al show that neural activity increases pSer-129 ~3-fold in primary culture, with no change in total α-synuclein 3 . This induction requires action potentials and synaptic transmission, indicating that network activity is responsible.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…In the current study, Ramalingam et al show that neural activity increases pSer-129 ~3-fold in primary culture, with no change in total α-synuclein 3 . This induction requires action potentials and synaptic transmission, indicating that network activity is responsible.…”
supporting
confidence: 53%
“…Dettmer, Selkoe and colleagues now address the physiological role of a post-translational modification associated with the synuclein + Lewy pathology characteristic of PD 3 . Considered specific for PD, phosphorylation of α-synuclein on Ser-129 (pSer-129) 4 has been widely used to assess the magnitude and extent of degeneration in animal models as well as the human condition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that in the presence of liposomes, αS becomes a better substrate for S129 phosphorylation by Plk2 in a cell‐free system (Ramalingam et al , 2023). This prompted us to explore the relationship, if any, between αS solubility and pS129 for fPD‐linked αS mutants, some of which are known to interfere with membrane interaction (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
“…It has been estimated that 90% of αS in Lewy lesions contains phospho‐serine‐129 (pS129), connecting this post‐translational modification to the pathology (Fujiwara et al , 2002). However, we recently demonstrated that pS129 is also of physiological relevance (Ramalingam et al , 2023). We discovered that (i) pS129 arises in response to synaptic activity, (ii) activity‐dependent pS129 is reversible and not associated with toxicity, (iii) activity‐dependent pS129 is catalyzed by Polo‐like kinase 2 (Plk2) downstream of calcineurin and counteracted by protein phosphatase 2A, (iv) αS incapable of phosphorylation (S129A) reduces the ratio of excitatory versus inhibitory spontaneous post‐synaptic currents, and (v) hippocampal plasticity is impaired in our novel S129A knock‐in mouse model.…”
Section: Introductionmentioning
confidence: 99%